PENERAPAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DALAM MENINGKATKAN KINERJA PADA PEGAWAI BAGIAN SEKRETARIAT DINAS PENDIDIKAN KOTA KEDIRI - Muzayadah, Nafisatul; Meilina, Restin; Muslih, Basthoumi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The purpose of this research is to study and measure the Organizational Citizenship Behavior (OCB) in improving the performance of the secretariat staff of the City of Kediri Education Office. There are five main aspects of OCB, namely: Altruism, Constiousness, Sportmanship, Civic Virtue, Courtesy. This study used descriptive qualitative method. Data collection conducted by researchers to the City of Kediri Education Office. The results of this study about the employees of the Secretariat of the Department of Education of the City of Kediri have done OCB well so as to improve performance.